TINGKAT WALKABILITY PADA KORIDOR JALAN DANAU TAMBLINGAN, KELURAHAN SANUR, KOTA DENPASAR - Koming Noziari; Ni Ketut Agusintadewi (Jurnal Arsitektur ARCADE, 2025)
Abstract: This study aims to analyze the level of walkability of pedestrian pathways (sidewalks) based on the Global Walkability Index (GWI) and to analyze the gap between user perception and expectation in the Jalan Danau Tamblingan corridor. The research object is the pedestrian pathway of Jalan Danau Tamblingan, and the subjects are its users. The methods used include the analysis of the GWI walkability level through field observation and a gap analysis of perception using a Likert-scale questionnaire. Sampling was conducted using a non-probability sampling technique of the accidental sampling type, involving a total of 99 respondents. The results show that the walkability level of Jalan Danau Tamblingan is classified as low to moderate. Although sidewalks are available, the low GWI score is primarily caused by a total failure in disability accessibility (identified as the most critical weakness), as well as high conflict with vehicles and inconsistent physical obstructions along the corridor. Significant improvement in walkability (to achieve a high GWI score) necessitates serious intervention in infrastructure repair and the implementation of universal design. The analysis of the perception and expectation gap also provides a guide for prioritizing the interventions most needed by users. Keyword: Walkability, Perception, Expectation. Abstrak: Penelitian ini bertujuan menganalisis tingkat walkability jalur pejalan kaki (trotoar) berdasarkan Global Walkability Index (GWI) dan menganalisis kesenjangan (gap) antara persepsi dan harapan pengguna di koridor Jalan Danau Tamblingan. Objek penelitian adalah jalur pejalan kaki Jalan Danau Tamblingan, dengan subjek penelitian adalah penggunanya. Metode yang digunakan mencakup analisis tingkat walkability GWI melalui observasi lapangan dan analisis gap persepsi menggunakan kuesioner berskala Likert. Pengambilan sampel dilakukan dengan teknik non-probability sampling jenis accidental sampling dengan total 99 responden. Hasil analisis menunjukkan bahwa tingkat walkability Jalan Danau Tamblingan tergolong rendah hingga sedang. Meskipun trotoar tersedia, skor rendah GWI disebabkan oleh kegagalan total dalam aksesibilitas disabilitas (menjadi kelemahan paling kritis), serta konflik tinggi dengan kendaraan dan hambatan fisik yang inkonsisten di sepanjang koridor. Peningkatan signifikan walkability (mencapai skor GWI tinggi) memerlukan intervensi serius pada perbaikan infrastruktur dan penerapan desain universal. Analisis gap persepsi dan harapan juga dapat memberikan panduan untuk memprioritaskan intervensi yang paling dibutuhkan pengguna. Kata Kunci: Walkability, Harapan, Persepsi.